Analyses of Shell Increment and Microgrowth Band Formation to Establish Seasonality of Mesolithic Shellfish Collection - Brook, Vibeke; Bouget, Edwin (Journal of Danish Archaeology, 1989)
Analyses of Shell Increment and Microgrowth Band Formation to Establish Seasonality of Mesolithic Shellfish Collection